On the Kura-Araxes expansion - Kosyan, Aram (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Towards the end of the 4th millennium BC Kura-Araxes culture of Transcaucasia (Early Transcaucasian culture) was terminated and later replaced by heterogeneous Kura-Araxes II. The settlements ceased to exist, in some cases due to destruction and/or conflagration. In archaeological literature had been expressed different views in regard to the termination of the Kura-Araxes I which mostly concern its possible causes. The study of this problem in the context of contemporary Near Eastern and Egyptian history and the so-called 5.2 k. BC climate event as well, the end of the Kura-Araxes I and the appearance of its different artifacts in Eastern Asia Minor, Lake Urmiya basin, and Syria-Palestine shows that, probably, this event was the result of global changes in the environment. The article is an attempt to suggest some remarks concerning the motives of the Kura-Araxes expansion, based upon the current understanding of this culture.